Unveiling the Ambrotype: Characterization of Two 19th Century Photographs - Costa, Leonor (2019)
This work used a multi-analytical approach to characterize two 19th century ambrotypes and was motivated by the lack of insight on these historical objects. Photographic imaging and optical microscopy (OM) were used to identify abrasions, cracks related to reticulation, tarnishing, and other aspects associated to production and degradation processes. With variable pressure scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (EDS) these processes were seen with great detail and further characterized. Elemental point analysis and elemental mapping showed that the photosensitive material used was silver iodide. Degradation compounds were found as silver and chlorine-containing compounds. In one of the items, the tarnishing area also contained redeposited silver in a ring-shape surrounding a nucleus rich in silver, copper, and sulfur, in addition to copper-based salts. EDS analyses also identified that the supports were common soda–lime–silica glasses, refined with arsenic; and showed that a pigment rich in iron was used in both items to hand color the cheeks, extended with aluminum silicates alone or mixed with barium sulfate. The μ-Raman study pointed out that a synthetic Mars pigment was employed. μ-Fourier-transform infrared spectroscopy analyses identified collodion as the binder. Shellac was used as a protective varnish in one of the items and a gum was possibly employed on the other. Bitumen was used for the background in one ambrotype.